PEMANFAATAN TEKNOLOGI DIGITAL SEBAGAI STRATEGI KOMUNIKASI PEMASARAN PADA PETERNAK KAMBING DI DUSUN SOLOT KABUPATEN PAMEKASAN - Widyananda, Cepryana Sathalica; Shamad, Zulfaini; Purdiyanto, Joko (Jurnal Terapan Abdimas, 2024)
Abstract. The important role of animal husbandry where its activities are part of agriculture that includes both processing, production facilities, cultivation, handling of maintenance and post-harvest periods and related marketing of its products. In Indonesia, goats are one of the most widely recognized small ruminants with very high productivity potential. Goats are used as small factories that produce meat and milk by some people in rural areas, in addition to meat and milk the results obtained from goats are skin and manure that can be used as fertilizer. The problems faced by farmers in Dusun Solot are the process of managing orders, expanding the market and managing waste from livestock. The objectives and benefits of this service activity are to provide knowledge and skills to farmers related to the use of digital technology in marketing activities such as the use of websites and social media and improve the ability of farmers to see business opportunities for beef goats and the use of livestock waste into organic fertilizer. The service method applied includes: preparation, implementation and assistance and evaluation. The results of this service activity on the utilization of  digital technology as a marketing communication strategy and the management and utilization of livestock waste provide new knowledge and skill for farmers in utilizing digital technology for marketing activities such as the use of website and social media, the ability of farmers to see business opportunities for beef goats and the utilization of livestock waste into organic fertilizer.  Abstrak. Peran penting peternakan dimana kegiatannya merupakan bagian dari pertanian yang mencakup usaha baik pengolahan, sarana produksi, budidaya, penanganan masa pemeliharaan dan pasca panen serta terkait pemasaran hasil produksinya. Di Indonesia, kambing adalah salah satu jenis ternak ruminansia kecil yang cukup dikenal luas dengan potensi produktivitas yang sangat tinggi. Kambing ini dimanfaatkan sebagai pabrik kecil yang menghasilkan daging dan susu oleh sebagian masyarakat di pedesaan, selain daging dan susu hasil yang didapat dari ternak kambing adalah kulit dan kotorannya yang dapat difungsikan sebagai pupuk. Permasalahan yang dihadapi oleh peternak yang ada di Dusun Solot yaitu proses mengelola pesanan, perluasan pasar serta pengelolaan limbah dari ternak. Adapun tujuan dan manfaat dari kegiatan pengabdian ini adalah untuk memberikan pengetahuan dan keterampilan pada peternak terkait pemanfaatan teknologi digital dalam kegiatan pemasaran seperti penggunaan website dan media social dan meningkatkan kemampuan peternak dalam melihat peluang usaha kambing potong serta pemanfaatan limbah ternak menjadi pupuk organik. Metode pengabdian yang diterapkan meliputi: persiapan, pelaksanaan dan pendampingan serta evaluasi. Hasil dari kegiatan pengabdian pemanfaatan teknologi digital sebagai strategi komunikasi pemasaran dan pengelolaan serta pemanfaatan limbah ternak ini memberikan pengetahuan dan keterampilan baru bagi para peternak dalam pemanfaatan teknologi digital untuk kegiatan pemasaran seperti penggunaan website dan media social, kemampuan peternak dalam melihat peluang usaha kambing potong serta pemanfaatan limbah ternak menjadi pupuk organik.